THE CENTRAL ROLE OF THE VILLAGE KIAI AS SIGNIFICANT OTHER IN RURAL MADURA - Totok Agus Suryanto; Huldiya Syamsiar; Muhammad Usamah Rasyidi (Penamas, 2023)
This research aims to comprehensively discuss the central role of the village kiai as a significant other in the social environment of rural Madurese society. The results of this study found twenty-two central roles of village kiai in carrying out social-religious activities in the social environment of the surrounding community. These include leading a four or seven-month pregnancy ceremony, a forty-day birth ceremony, a ceremony to descend the land, giving names to newborn children, giving consideration to choosing a potential life companion, solutions to plans to build a house, leading a wedding party, giving prayers for blessings, prayers when children are in the process of weaning, determining the implementation of the marriage contract process and the wedding party, giving prayers for safety during the wedding party, leading a seven-day death ceremony, and other social events in the local community. Meanwhile, the method used is descriptive qualitative, with a snowball sampling procedure to the kiai as the subject of the research. While the data analysis technique uses data reduction, data presentation to conclusion drawing.